Analisis Penerapan SAK ETAP Pada BUMDes Luhur Sepakat Desa Sido Luhur Kabupaten Bengkulu Utara - Ferina, Zahrah Indah; Rozalia, Siti; Anitasari, Merri (Disclosure: Journal of Accounting and Finance, 2021)
The purpose of this study is to examine whether the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in BUMDes Luhur Sepakat financial statements have gone well in accordance with SAK ETAP in which there are balance sheets, income statements, statements of changes in equity, statements of cash flows and records on the financial statements. BUMDes Luhur Sepakat is one of the BUMDes in Padang Jaya District. The initial capital source for the formation of BUMDes comes from the Village Budget (APB desa). To answer the problems regarding the application of financial statements, the data analysis method used in this study is a comparative method by comparing SAK ETAP and BUMDes Luhur Sepakat financial statements. The results of this study showed that the financial report of BUMDes Luhur agreed Sido Luhur Village has not matched the SAK ETAP. Balance sheet and Income statement are made correctly. BUMDes Luhur agreed not to make statements of cash flows, equity changes reports, and records of financial statements.Â The reporting of financial information continues to be done routinely, and the caretaker BUMDes Luhur agreed already accountable for the financial report with the deliberation to the community at the end of the year.